Perempuan Alor di Pusaran Budaya Belis: Sebuah Pendekatan Etnografis Melalui Revitalisasi Budaya - Anil Dawan (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2019)
This article discusses about women in Alor in the Belis vortex in a dilemma that limits its empowerment efforts. Cultural revitalization is closely related to the issue of child protection and empowerment of women, therefore it is necessary to reconstruct existing and ongoing social constructs, but it has an impact on systematic impoverishment, where women's rights and children's basic rights are not met. The revitalization process starts from the perspective that influences human life in terms of race, religion, ethnicity and community. This research method uses qualitative ethnography to photograph the lives of Alor women in the vortex of Belis culture and how it impacts on women's empowerment. especially education and well-being. The result was the collective awareness of 3 Triple Helix (three stoves, namely traditional leaders, religious leaders and the government). Collective awareness results from a long process of journey and combinatorial collaboration between people who want to change, middle people who become assistants and change facilitators and the government as a key stake holder that provides power, funding and prayer support. Keywords: cultural revitalization, empowerment of women, belis